Visualizing Dynamic Performance of Lipid Droplets in a Parkinson’s Disease Model via a Smart Photostable Aggregation-Induced Emission Probe - Li, Lihua; Zhou, Fan; Gao, Qun; Lu, Yao; Xu, Xingyi; Hu, Rong; Wang, Zhiming; Peng, Mingying; Yang, Zhongmin; Tang, Ben Zhong (iScience, 2019)
Parkinson’s disease (PD) is a complex neurodegenerative disease affected by diverse factors, and lipid droplets (LDs) are increasingly recognized as major players in PD because of their relevance to neuron activity. However, long-term dynamic changes of LDs and their relative activity remain unclear. Here, an aggregation-induced emission (AIE) probe named 2-DPAN was prepared and employed to visualize dynamic processes of LDs in a 6-hydroxydopamine model of PD for the first time, and LDs' accumulation-peak/plateau-decrease were confirmed. We further found a close relationship between LDs and variation in mitochondrial activity. Strikingly, the progression of cell death was accelerated by lipase, whereas pre-stimulation of LDs by unsaturated fatty acid-oleic acid decreased the death process by inhibiting excessive reactive oxygen species (ROS) and fatty acid production, thereby protecting mitochondria. The utilization of 2-DPAN demonstrates the importance of LDs in neuronal homeostasis, and effective tuning of LDs may prevent or inhibit PD progression. [Display omitted] •2-DPAN monitors the dynamic changes of Lipid droplets (LDs) in Parkinson disease•LDs' dynamic change process including three phases, accumulation-plateau-decrease•LDs' change trend was highly correlated with mitochondrial disruption•Efficient tuning of LDs could slow the PD progress Disease; Chemical Synthesis; Materials Design